A new hybrid sewage treatment system combining a rolled pipe system and membrane bioreactor to improve the biological nitrogen removal efficiency: A pilot study. (20th March 2018) - Bach, Quang-Vu; Le, Van Tam; Yoon, Yong Soo; Bui, Xuan Thanh; Chung, Woojin; Chang, Soon Woong; Ngo, Huu Hao; Guo, Wenshan; Nguyen, Dinh Duc
Abstract: A new hybrid pilot plant configuration based on a modularized rolled pipe system (RPS) combined with a submerged flat sheet membrane bioreactor (MBR) was investigated to enhance the sewage treatment and membrane performance. The system was operated under actual conditions for more than four months, that is, at a constant flow rate of 30 m³/d and with two internal recycling ratios. The results indicate that the hybrid system produces an excellent effluent quality and considerably mitigated membrane fouling. The average concentrations of SS, COD, TN, NH4 + -N, NO3 − -N, and PO4 3- -P remained below 2.81, 8.29, 8.77, 0.15, 8.17, and 1.49 mg/L, respectively. It was estimated that the periodic chemical cleaning of the membrane could be extended to approximately six months. The MBR and RPS can virtually complete nitrification and denitrification, respectively. The highest average denitrification rate of the RPS is 116.95 mg NO3 -N/(g MLVSS d), with a hydraulic retention time of 1.05 h. Therefore, the RPS–MBR hybrid system has potential to improve the sewage treatability. The emerging RPS technique can obtain high rates of denitrification coupled with a compact design, ease of installation, and small footprint. Graphical abstract: Image 1 Highlights: A new hybrid sewage treatment system was explored. Excellent denitrification is achieved with the novel rolled pipe system. High rates of simultaneous nitrification and denitrification are obtained. The hybrid system performs well in removing organic and nitrogen compounds. The membrane fouling rate of the hybrid system is significantly low.